A Multivariate Analysis of Clinical Severity, Psychological Distress and Psychopathological Traits in Psoriatic Patients - Kotrulja, Lena (Array, 2010)
Psoriasis is a chronic skin disease associated with problems in body image and self-esteem and feelings of stigma and shame. The aim of this study was to analyse the clinical extent of psoriasis and its association with psychological distress, and to compare the psychopathological traits in early-onset (type I: age of onset < 40 years) vs. late-onset (type II: age of onset > 40 years) psoriasis. A total of 140 patients participated in the study ; 70 patients with confirmed diagnosis of psoriasis vulgaris and 70 patients as a comparative group. A battery of psychological instruments was used together with an Inventory of life stress events. The severity of psoriasis was assessed by standardized Psoriasis Area and Severity Index measure. The Psoriasis Life Stress Inventory showed the significant correlation with clinical extent of psoriasis and other measures of psychological distress. Patients with late-onset psoriasis had more prominent symptoms of depression compared with the group with early-onset psoriasis and the comparative group. The results of the Minnesota Multiphasic Personality Inventory-201 for the patient group with late-onset psoriasis showed a specific configuration of neurotic triad.